2017
DOI: 10.1002/bjs.10527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the peritoneal carcinomatosis index with CT and MRI

Abstract: The combination of CT and MRI improved the preoperative estimation of PCI compared with CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 19 publications
0
52
0
3
Order By: Relevance
“…Improving patient selection is therefore reliant on the ability to predict accurately the extent of peritoneal metastasis and the ability to resect it completely. Specialist radiologists have demonstrated good concordance between radiological and surgical PCI estimations, particularly when combining modalities; however, these tend to be most accurate in patients with high PCI scores 57,58 . In some centres this is used in combination with diagnostic laparoscopy before CRS + HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…Improving patient selection is therefore reliant on the ability to predict accurately the extent of peritoneal metastasis and the ability to resect it completely. Specialist radiologists have demonstrated good concordance between radiological and surgical PCI estimations, particularly when combining modalities; however, these tend to be most accurate in patients with high PCI scores 57,58 . In some centres this is used in combination with diagnostic laparoscopy before CRS + HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are comparable with those of smaller pilot studies on the assessment of PM with DW‐MRI. In a population of patients with appendiceal and ovarian cancer, Low and co‐workers reported that, compared with S‐PCI, DW‐MRI correctly categorized tumour volume in 91 per cent of patients as opposed to only 50 per cent with CT. Interestingly, a recent meta‐analysis proposed CT as the preferred imaging modality for detection of PM. This conclusion, however, was based on the robustness of CT data, given the minority of available MRI studies (19 versus 3).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a well known high understaging rate of the PCI assessed by CT, this remains the imaging method of choice in most centres. The combination of contrast‐enhanced MRI with diffusion‐weighted (DW) imaging has shown promising results for assessing the PCI. The latter studies, however, were retrospective and either small or heterogeneous, including patients with PM originating from other malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…2123 Unfortunately, each technique has some intrinsic limitations, such as low contrast resolution for CT and low spatial resolution for MRI and positron emission tomography-CT, resulting in a consistent underestimation of the PM spread mostly because of false-negatives of thin or small lesions less than 1 cm. 2428 In addition, none of these 3 techniques allows spectral capabilities such as differentiation of 2 contrast agents.…”
mentioning
confidence: 99%